2020
DOI: 10.1186/s12902-020-0540-7
|View full text |Cite
|
Sign up to set email alerts
|

Plasma adiponectin, visfatin, leptin, and resistin levels and the onset of colonic polyps in patients with prediabetes

Abstract: Background: Prediabetes is associated with a high risk of colon cancer, and abdominal obesity, which can result in the secretion of several obesity-related adipocytokines, is an independent influencing factor for colonic polyps in prediabetes subjects. However, the correlation between adipocytokine levels and colonic polyps in prediabetes subjects is unclear. This research explores the relationship between plasma adiponectin, visfatin, leptin, and resistin levels and the development of colonic polyps in predia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…In this study, we firstly revealed the differences of adiponectin, nesfatin-1, IL-6, and TNF-a between prediabetes and T2DM or healthy individuals in Chinese population. Our results disclosed that adiponectin levels in prediabetes were distinctly lower than those in the healthy, while no significant difference was observed when compared to those in T2DM, which was consistent with the consequences of previous studies (30,31). Our data also proved that nesfatin-1 levels in prediabetes were obviously higher than those in T2DM but no significant difference when compared to those in the healthy, which is the first delineation, despite the fact that others demonstrated mildly lower nesfatin-1 levels in impaired fasting glycemia and impaired glucose tolerance in contrast to those in the healthy group (21).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we firstly revealed the differences of adiponectin, nesfatin-1, IL-6, and TNF-a between prediabetes and T2DM or healthy individuals in Chinese population. Our results disclosed that adiponectin levels in prediabetes were distinctly lower than those in the healthy, while no significant difference was observed when compared to those in T2DM, which was consistent with the consequences of previous studies (30,31). Our data also proved that nesfatin-1 levels in prediabetes were obviously higher than those in T2DM but no significant difference when compared to those in the healthy, which is the first delineation, despite the fact that others demonstrated mildly lower nesfatin-1 levels in impaired fasting glycemia and impaired glucose tolerance in contrast to those in the healthy group (21).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, we rstly revealed the differences of adiponectin, nesfatin-1, IL-6 and TNF-α between prediabetes and T2DM or healthy individuals in Chinese population. Our results demonstrated that adiponectin levels in prediabetes were distinctly lower than that in the healthy, while no signi cant difference was observed when compared to T2DM, which was consistent with the consequences of previous studies [30,31] . Another research reported signi cant reduction of adiponectin in impaired fasting glucose group compared with hyperglycemic group [31] .…”
Section: Discussionsupporting
confidence: 93%
“…However, the exact and discrete pathophysiological links between obesity and T2DM are not yet fully elucidated. There is enough evidence to suggest that changes in adipocytokine secretion do contribute to defective insulin production/action and, concomitantly, result in peripheral insulin resistance [ 13 , 14 , 15 , 16 , 17 ]. Adipokines such as adiponectin, leptin resistin, visfatin, ghrelin and chemerin seem to play an important role in the onset, progression and complications of T2DM [ 14 , 17 , 18 , 19 , 20 , 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%